68‐3: Study on Relation between Fluorescent Dye Combination and Process Temperature as Photoresist. Issue 1 (30th May 2018) - Lee, Seungbeom; Kim, Sooin; Kim, Wonrae; Kim, Younghoon; Kwak, Musun; Lee, Jounho; Jun, Mike; Kang, Inbyeong
Abstract : Suggested additional layer of fluorescent dye combination and proper process temperature condition as photoresist (PR) optimize the display between white organic light emitting diode (WOLED) and color filter (CF). As a result, this application have an effective way to increase color coverage and shows that the PL intensity area at the post‐bake condition below 200℃ is 13% higher than above 200℃.